Card posting does not rely on visual orientation: A challenge to past neuropsychological dissociations. (20th August 2021) - Hesse, Constanze; Bonnesen, Kamilla; Franz, Volker H.; Schenk, Thomas
Abstract: A common set of tasks frequently employed in the neuropsychological assessment of patients with visuomotor or perceptual deficits are the card-posting and the perceptual orientation matching tasks. In the posting task, patients have to post a card (or their hand) through a slot of varying orientations while the matching task requires them to indicate the slot's orientation as accurately as possible. Observations that damage to different areas of the brain (dorsal vs. ventral stream) is associated with selective impairment in one of the tasks - but not the other - has led to the suggestion that different cortical pathways process visual orientation information for perception versus action. In three experiments, we show that this conclusion may be premature as posting does not seem to rely on the processing of visual orientation information but is instead performed using obstacle avoidance strategies that require an accurate judgement of egocentric distances between the card's and the slot's edges. Specifically, we found that while matching is susceptible to the oblique effect (i.e., common perceptual orientation bias with higher accuracy for cardinal than oblique orientations), this was not the case for posting, neither in immediate nor in memory-guided conditions. In contrast to matching, posting errors primarily depended on biomechanical demands and reflected a preference for performing efficient and comfortable movements. Thus, we suggest that previous dissociations between perceptual and visuomotor performance in letter posting tasks are better explained by impairments in egocentric and allocentric spatial processing than by independent visual processing systems. Highlights: Letter posting performance is not affected by the oblique effect. Orientation errors in posting are determined by rotation requirements (effort). Matching, but not posting, relies on orientation information. Posting can be better understood as an obstacle avoidance task. Dissociations in matching versus posting do not support perception-action model.